Automation of APAAP immunocytochemical technique. - Stross, W P (1989)
A tissue processing instrument (the Histokinette) was modified by the addition of an electronic timing device which allows an immunocytochemical staining technique (the APAAP method) to be performed as a semiautomated procedure. After incubation with primary monoclonal antibodies (applied by hand) slides (up to 72 in a batch) are placed in racks and cycled through tanks of reagents, comprising anti-mouse Ig followed by APAAP complexes with intervening timed draining and washing stages. This semiautomated process gave consistent staining results and offered considerable savings in time compared with conventional methods. The same reagent baths were used over four months on an almost daily basis without deterioration in staining intensity, and consequently the calculated overall cost of the staining procedure was less than if the reagents had been applied by hand and then discarded. The machine is now into its eleventh month of operation; the reagents have been changed twice. It is suggested that this approach, because of savings in time and increased consistency, may be an attractive technique for the routine immunocytochemical staining of slides, and that the nature of the APAAP method is particularly suitable for automation as the necessary reagents can be produced at low cost.